CaPaBLE - Assessing the Patient Generated Index Methodology in High Grade Glioma Patients and Caregivers. (1st October 2022) - Pakzad-Shahabi, Lillie; Tallant, James; Le Calvez, Kerlann; Wells, Mary; Williams, Matt
Abstract: AIMS: CaPaBLE tests the feasibility and acceptability of assessing quality of life (QoL) using the patient-, or caregiver-generated index (PGI/CaGI) methodology in patients with HGG and their caregivers. METHOD: CaPaBLE, (https://www.isrctn.com/ISRCTN45555598 ), followed patients and/or their caregivers up to 6 months. Standard measures for patients were EORTC QLQ-C30/BN20, for caregivers the CarGOQOL questionnaire. The QoL topics raised through PGI/CaGI have been coded to the most relevant domain from their respective standard measure for an initial assessment of concordance. RESULTS: 36 patients, 24 caregivers recruited to study; completing an average of 3 study assessment timepoints. PGI and CaGI generated 240 and 160 topics respectively. Patient concerns most frequently coded to EORTC domain of Role Functioning; Caregiver concerns mostly coded to CarGOQOL domain of Burden. Other topics frequently raised by patients such as the driving and sex life, and future planning by caregivers are not specifically raised in standard questionnaires. CONCLUSION: Nearly all topics raised by patients and caregivers were mapped to the domains of their respective standard QoL measure. However, almost half of all topics raised by patients and caregivers mapped to a minority of the domains included in standard measures; whilst a notable number of topics are not specifically included in standard measures at all. This raises questions regarding the efficiency and relevance of such questionnaires to patient and caregivers' daily lives.